CdTe-based crystals with Mg, Se, or Mn as materials for X and gamma ray detectors: Selected physical properties. Issue 4 (November 2021) - Mycielski, Andrzej; Wardak, Aneta; Kochanowska, Dominika; Witkowska-Baran, Marta; Szot, Michał; Jakieła, Rafał; Domagała, Jarosław Z.; Kowalczyk, Leszek; Kochański, Michał; Janusz, Gabriela; Dopierała, Marcin; Marciniak, Adam; et al.
Abstract: In recent years, a series of investigations has been devoted to a possibility of using crystals based on CdTe with addition of magnesium (Mg), selenium (Se), or manganese (Mn) for X and gamma radiation detectors. In the literature there are contradictory data with respect to the segregation of Mg in (Cd, Mg)Te and Se in Cd(Te, Se) and to the possibility of obtaining materials with a homogeneous composition without grains and twins. We have wide technological possibilities of preparing crystals and investigating some of their properties. Thus, we performed crystallizations of (Cd, Mg)Te, Cd(Te, Se), (Cd, Mn)(Te, Se), and (Cd, Mn)Te compounds. The aim of our studies was to check whether any of the investigated materials may be easily obtained by the Low Pressure Bridgman (LPB) method in the form of large, homogeneous, high resistivity single crystals with as few as possible twins, subgrains, and tellurium inclusions. The crystallization processes were performed by using the LPB method. The elements used: Cd, Te, Mn, Mg, and Se were of the highest purity available at that time. In order to obtain reliable conclusions the crystallization processes were carried out under identical technological conditions. The details of our technological method and the results of the investigation of physical properties of the samples are presented below.